INDONESIAN LANGUAGE DEVELOPMENT IN THE DIGITAL AGE: CHALLENGES AND INNOVATIONS - Ni Putu Parmini; I Wayan Mawa; I Made Suparta; I Gede Bagus Wisnu Bayu Temaja (Adisam Publisher, 2025)
Indonesian language is undergoing significant changes in the digital era, facing complex challenges and opportunities. Globalisation and technological developments threaten the dominance of the Indonesian language with the increasing use of foreign languages, especially English, on various digital platforms. However, innovations in linguistic technology offer potential solutions to maintain and develop the Indonesian language in the digital world. Technologies such as natural language processing (NLP), automatic translation, and speech recognition play an important role in ensuring the accessibility and relevance of the Indonesian language. Concerted efforts from the government, academia and the tech industry are needed to address these challenges and promote wider and more effective use of Indonesian in the digital age.